Impact Of Water Dynamics Land On Rate And Time Of Peat Swamp Land Subsidence Tropika - L. Budi Triadi; Hengky F. Adji; Arif Dhiaksa (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Changes in land use of tropical peat will lead to the release of carbon (C) on the condition that initially stabilized, and resulting in land subsidence. Peatland clearance which is preceded by the construction of the canals will cause the ground water table in peatlands fell. Along with that, the subsidence occurs, which at the beginning of peatland reclamation rate of decline very fast and gradually slow down over time with reduction of organic materials that decompose or burn. Therefore, knowledge of the rate of subsidence is very important to plan drainage and optimal use of peat land in order to preserve the peat. The method or scientific approach used is the assessment directly, include: measurement of the location of groundwater levels, land subsidence at various existing condition of land in different locations, peat soil sampling and calculation with the empirical formula. The calculation of land subsidence using average data groundwater levels during the dry season, in addition to the types of land cover took into account as well. This paper presented the results of the analysis of land subsidence and the projected decline in the next 50 years peatlands in Sei Ahaz, Kapuas, Central Kalimantan and Sungai Buluh, Tanjung Jabung, Jambi and comparative results between the two locations. The implications of this study indicate that the regulation of groundwater levels will control land subsidence.